An Initial Genome Editing Toolset for Caldimonas thermodepolymerans, the First Model of Thermophilic Polyhydroxyalkanoates Producer - Grybchuk-Ieremenko, Anastasiia; Lipovská, Kristýna; Kouřilová, Xenie; Obruča, Stanislav; Dvořák, Pavel (Microbial biotechnology, 2025)
The limited number of well-characterised model bacteria cannot address all the challenges in a circular bioeconomy. Therefore, there is a growing demand for new production strains with enhanced resistance to extreme conditions, versatile metabolic capabilities and the ability to utilise cost-effective renewable resources while efficiently generating attractive biobased products. Particular thermophilic microorganisms fulfil these requirements. Non-virulent Gram-negative Caldimonas thermodepolymerans DSM15344 is one such attractive thermophile that efficiently converts a spectrum of plant biomass sugars into high quantities of polyhydroxyalkanoates (PHA)-a fully biodegradable substitutes for synthetic plastics. However, to enhance its biotechnological potential, the bacterium needs to be 'domesticated'. In this study, we established effective homologous recombination and transposon-based genome editing systems for C. thermodepolymerans. By optimising the electroporation protocol and refining counterselection methods, we achieved significant improvements in genetic manipulation and constructed the AI01 chassis strain with improved transformation efficiency and a ΔphaC mutant that will be used to study the importance of PHA synthesis in Caldimonas. The advances described herein highlight the need for tailored approaches when working with thermophilic bacteria and provide a springboard for further genetic and metabolic engineering of C. thermodepolymerans, which can be considered the first model of thermophilic PHA producer.
Keywords: gene deletion; genetic engineering; Caldimonas thermodepolymerans; Metabolic Engineering; editace genu; polyhydroxyalkanoates; Homologous Recombination; Genome, Bacterial; transpozibilní elementy DNA; homologní rekombinace; Gene Editing; Polyhydroxyalkanoates; genom bakteriální; Electroporation; DNA Transposable Elements; polyhydroxyalkanoáty; metabolické inženýrství; elektroporace; thermophiles